The evolution of the hospital from antiquity to the end of the middle ages - L. Cilliers; F.P. Retief (AOSIS, 2002)
The evolution of the hospital is traced from its onset in ancient Mesopotamia towards the end of the 2nd millennium to the end of the Middle Ages. Reference is made to institutionalised health care facilities in India as early as the 5th century BC, and with the spread of Buddhism to the east, to nursing facilities, the nature and function of which are not known to us, in Sri Lanka, China and South East Asia. Special attention is paid to the situation in the Graeco-Roman era: one would expect to find the origin of the hospital in the modem sense of the word in Greece, the birthplace of rational medicine in the 4th century BC, but the Hippocratic doctors paid house-calls, and the temples of Asclepius were visited for incubation sleep and magico-religious treatment. In Roman times the military and slave hospitals which existed since the 1st century AD, were built for a specialized group and not for the public, and were therefore also not precursors of the modem hospital. It is to the Christians that one must turn for the origin of the modem hospital. Hospices, initially built to shelter pilgrims and messengers between various bishops, were under Christian control developed into hospitals in the modem sense of the word. In Rome itself, the first hospital was built in the 4th century AD by a wealthy penitent widow, Fabiola. In the early Middle Ages (6th to 10th century), under the influence of the Benedictine Order, an infirmary became an established part of every monastery. During the late Middle Ages (beyond the 10th century) monastic infirmaries continued to expand, but public hospitals were also opened, financed by city authorities, the church and private sources. Specialized institutions, like leper houses, also originated at this time. During the Golden Age of Islam the Muslim world was clearly more advanced than its Christian counterpart with magnificent hospitals in various countries.